Induced Vacuum Polarization of Scalar Field by Impenetrable Magnetic Tube - Gorkavenko, V.M.; Sitenko, Yu.A.; Stepanov, O.B. (Відділення фізики і астрономії НАН України, 2010)
We investigate the influence of an external magnetic field in a tube on the vacuum of a massive charged scalar field for arbitrary space-time dimensions. The tube is considered impenetrable for the scalar field and obeys the Dirichlet boundary condition on the bounding surface. It was shown that, for a particular case of the 2 + 1-dimensional space-time, the induced vacuum energy of the scalar field outside the tube can be numerically calculated without regularization procedure. The dependences of the induced vacuum energy upon the distance from the tube at its various transversal radii are obtained. У роботi дослiджено узагальнену на випадок простору-часу довiльної розмiрностi задачу про вплив на вакуум зарядженого масивного скалярного поля зовнiшнього магнiтного поля, розташованого в трубцi скiнченого радiуса. Трубка є непроникливою для бозонного поля та має на поверхнi граничнi умови типу Дiрiхле. Показано, що для часткового випадку просторучасу розмiрнiстю 2+1 iндукована густина енергiї вакууму ззовнi трубки може бути знайдена чисельними методами без застосування процедури регуляризацiї. Отримано залежностi iндукованої густини енергiї вакууму вiд вiдстанi до трубки при рiзних значеннях її поперечного радiуса.